2016
DOI: 10.3390/e18030101
|View full text |Cite
|
Sign up to set email alerts
|

A Complexity-Based Approach for the Detection of Weak Signals in Ocean Ambient Noise

Abstract: Abstract:There are numerous studies showing that there is a constant increase in the ocean ambient noise level and the ever-growing demand for developing algorithms for detecting weak signals in ambient noise. In this study, we utilize dynamical and statistical complexity to detect the presence of weak ship noise embedded in ambient noise. The ambient noise and ship noise were recorded in the South China Sea. The multiscale entropy (MSE) method and the complexity-entropy causality plane (C-H plane) were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…At the same time, SR-N signals are the basis for the development, testing and use of these naval equipment. Due to the marine environmental noise and the time-varying characteristics of the underwater acoustic channel, the measured SR-N signal is a nonlinear and non-stationary chaotic signal [5,6]. Noise reduction of SR-N signal is beneficial to further feature extraction, classification and detection [7].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, SR-N signals are the basis for the development, testing and use of these naval equipment. Due to the marine environmental noise and the time-varying characteristics of the underwater acoustic channel, the measured SR-N signal is a nonlinear and non-stationary chaotic signal [5,6]. Noise reduction of SR-N signal is beneficial to further feature extraction, classification and detection [7].…”
Section: Introductionmentioning
confidence: 99%
“…SN signal contains more characteristic parameters of ship, which is an important indicator of the performance of ship. Therefore, the denoising and feature extraction for SN are critical technologies in the underwater acoustic field [1]. Due to the presence of noise, the physical characteristics of real signal are covered up.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is caused by the broadband signal and its interaction with the measured element. Several related papers [4][5][6][7][8][9] introduce and discuss various applications of noise spectroscopy, utilizing tests of periodic materials and metamaterials. The research performed to date has nevertheless shown that, for evaluating and comparing the quantitative values monitored during the assessment of properties of periodic structures via noise spectroscopy, the approach based on the description of the frequency spectrum is considerably ineffective and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, from a broader perspective, an interesting attempt to challenge traditional detection concepts was proposed by Yang et al, whose algorithms and theorems outlined within the above-referenced paper [7] may embody a viable solution to some of the drawbacks that affect current procedures within signal detection and noise processing. Certain fields and disciplines, then, utilize substantially simplified theoretical tools [6] or analyses based on decomposing the resulting signal into elements of infinite or wide series [7]; similarly, stochastic instruments are also employed, complementing the two previously mentioned approaches that enable the description of large-scale systems as a nondeterministic model of research [8]. In such solutions, it is usually suitable to consider the origin and source of the ultra-wideband (UWB) signal.…”
Section: Introductionmentioning
confidence: 99%